Prognostic Value of Serum Lactate Dehydrogenase in Renal Cell Carcinoma: A Systematic Review and Meta-Analysis. - Jie Shen; Zhen Chen; Qianfeng Zhuang; Min Fan; Tao Ding; Hao Lu; Xiaozhou He (PLoS ONE)
Background Recently, many studies have shown that the serum lactate dehydrogenase (LDH) level is related to the prognosis of renal cell carcinoma (RCC). We launched this meta-analysis to assess the prognostic value of serum LDH in patients with RCC. Methods We searched PubMed, Embase and Web of Science for information on serum LDH and the outcome of RCC through June 14, 2016. The hazard ratio (HR) and its 95% confidence interval (CI) for overall survival (OS) and progression-free survival (PFS) were extracted and integrated from the matching studies. Results A total of 29 studies including 6629 patients with RCC were incorporated in this meta-analysis. Patients whose serum LDH levels were elevated had a lower OS (HR = 2.13, 95% CI = 1.69-2.69, P < 0.001). Meanwhile, the pooled data showed that a higher serum LDH level was a negative prognostic factor for PFS (HR = 1.74, 95% CI = 1.48-2.04, P < 0.001). Furthermore, subgroup analyses indicated elevated serum LDH was associated with poor survival in different tumor types. Elevated serum LDH was significantly associated with worse prognosis for patients with all stages of RCC (OS, HR = 2.41, 95% CI = 1.09-5.33), metastatic RCC (OS, HR = 2.62, 95% CI 1.57-2.59; CSS, HR = 1.79, 95% CI 1.49-2.15), and non-metastatic RCC (OS, HR = 3.67, CI = 1.33-10.13). Besides, elevated serum LDH also indicated a worse prognosis in subgroups of cut-off values, analysis types and ethnicity. Conclusions Our results show that serum LDH levels are associated with the outcomes of RCC and can be used as a valuable biomarker for monitoring prognoses.